2017
DOI: 10.1002/jcla.22121
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different enzyme‐linked immunosorbent assay methods for avidity determination of antiphospholipid antibodies

Abstract: This way was in good agreement with more demanding procedures. Both urea and sodium chloride may be used as chaotropic agents. Reference values of avidity indices essential for interpretation of patients' results must be established individually for distinct assay conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 31 publications
1
24
0
1
Order By: Relevance
“…The avidity index (AI) of anti-CSP antibodies was evaluated using an ELISA-based chaotrope avidity assay 52 . This protocol followed the standard ELISA (described above), except that following serum incubation wells were treated with 6M urea for 10 minutes.…”
Section: Measurement Of Antibody Aviditymentioning
confidence: 99%
“…The avidity index (AI) of anti-CSP antibodies was evaluated using an ELISA-based chaotrope avidity assay 52 . This protocol followed the standard ELISA (described above), except that following serum incubation wells were treated with 6M urea for 10 minutes.…”
Section: Measurement Of Antibody Aviditymentioning
confidence: 99%
“…A variety of methods and their modification for antibody avidity has already been described [11,30]. Recently, we explored in detail aCL IgG avidity methods using the principle of ELISA with chaotropes, which break the interactions of low-avidity antibodies with antigens [18]. A higher concentration of chaotropic agents caused more effective disruption of immune complexes.…”
Section: Discussionmentioning
confidence: 99%
“…We found that both urea in concentrations of 6 mol/l or 8 mol/l and sodium chloride in concentrations of 1 mol/l or 2 mol/l were suitable for the sufficient dissociation of immune complexes during an extra step in the ELISA procedure. The extended description of the ELISA for avidity examination using chaotropic agents is shown in Fialová et al [17,18]. For the purpose of this study, we used sera diluted 1:50 and urea in concentrations of 6 mol/l and 8 mol/l as a chaotrope.…”
Section: Avidity Of Acl Iggmentioning
confidence: 99%
See 1 more Smart Citation
“…La urea es un agente caotrópico que afecta los enlaces de hidrógeno, desestabilizando las fuerzas hidrófobas que actúan en la unión antí genoanticuerpo. Las uniones débiles se rompen, quedando unidas las que tienen mayor afinidad funcional o avidez (Fialová et al, 2017). Este efecto es similar al logrado cuando los sueros son absorbidos con otras micobacterias, como Myco bacterium phlei (Di Paolo et al, 2016; OIE, 2018.…”
Section: Introductionunclassified